Rimski lonček s Ptuja z napisom v neznani pisavi in v staroselskem, domnevno keltskem jeziku - Eichner, Heiner; Istenič, Janka; Lovenjak, Milan (Arheološki vestnik, 1994)
The paper discusses the discovery of an inscribed small pot from the vvestern graveyard of Poetovio. The pot is dated from the 2n<l or 3rd centuries AD. and although the inscription, which is scratched on the pot, has certain similarities with the Venetian alphabet. the script appears to be a local variant. The names mentioned indicate a Celtic influence. The article concludes with a discussion on the likely ethnic composition of Poetovio.